Epidemiological profile of nonmelanoma skin cancer in renal transplant recipients: experience of a referral center - Ferreira, Flávia Regina (Sociedade Brasileira de Dermatologia, 2014)

(untitled)
BACKGROUND: Nonmelanoma skin cancer is the most common form of cancer in humans and also the malignant disease that is increasingly common among kidney transplant recipients. OBJECTIVE: To determine the epidemiological characteristics of renal transplant recipients with nonmelanoma skin cancer seen at a referral transplantation center. METHODS: Cross-sectional descriptive study with renal transplant recipients presenting nonmelanoma skin cancer, treated at a transplantation referral center between 08/01/2004 and 08/31/2009. Analyzed variables were: gender, age, skin phototype, occupational and recreational sun exposure, use of photoprotection, personal and family history of non-melanoma skin cancer, clinical type and location, time between transplantation and the appearance of the first nonmelanoma skin cancer, occurrence of viral warts, timing of transplantation, type of donor, cause of kidney failure, previous transplants, comorbidities, pre-transplant dialysis, type and duration of dialysis. RESULTS: 64 subjects were included. Males - 71.9%; low skin phototypes (up to Fitzpatrick III) - 89%; mean age - 57.0 years - and mean age at transplant - 47.3 years; sun exposure - 67.2% occupational - and 64.1% recreational; photoprotection - 78.2% (although only 34.4% in a regular manner); squamous cell carcinoma - 67.2%; squamous cell carcinoma/basal cell carcinoma ratio - 2:1; personal history of nonmelanoma skin cancer - 25% - and family history - 10.9%; location at photoexposed area - 98.4%; average latency time between transplantation and first nonmelanoma skin cancer appearance - 78.3 months; viral warts (HPV) after transplant - 53.1%; average timing of transplantation - 115.5 months; living donor - 64.1%; triple regimen (antirejection) - 73.2%; comorbidities - 92.2%; pre-transplant dialysis - 98.4%; hemodialysis - 71.7%; average duration of dialysis - 39.1 months; previous transplants - 3.1%; hypertension as cause of renal failure - 46.9%. CONCLUSION: This study allowed the epidemiological characterization of a population of kidney transplant recipients with nonmelanoma skin cancer.